Familial dysequilibrium-diplegia with T-lymphocyte deficiency. Issue 12 (December 1975) - Graham-Pole, J; Ferguson, A; Gibson, A A; Stephenson, J B
Abstract : A second family is described with a combination of defective thymus-dependent immunity and cerebral palsy. The cerebral palsy comprised nonprogressive dysequilibrium and mild spastic diplegia without limb ataxia. This genetic entity of presumed autosomal recessive inheritance is clearly distinguished from ataxia-telangiectasia. Immunological abnormalities should be sought in other familial or unexplained cerebral palsy syndromes.